Tunneling dynamics in cryocrystals: localization and delocalization: Electronically Induced Phenomena - Storchak, Vyacheslav G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
The phenomenon of quantum diffusion of muonium in cryocrystals with rotational degrees of freedom is discussed. The quantum tunneling dynamics and electron transport are considered takinginto account the effects of disorder.